“WE FACE OBSTACLES WITH IKHLAS”: REFLECTION ON PSYCHOLOGICAL FLEXIBILITY OF ELEMENTARY SCHOOL TEACHERS IN RURAL TEGAL, CENTRAL JAVA, DURING COVID-19 PANDEMIC - Pramesti, Maulida Amalia; Hayati, Elli Nur; Bashori, Khoiruddin (Islamic Psychology Study Program, Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study examines the psychological flexibility of elementary school’s teachers in rural settings who obliged to still carried out teaching activities during Covid-19 pandemics. The changing teaching methods, along with other daily life changes, are common to be studied in urban setting. But, the vulnerable group of teachers in rural community setting is under researched. The school in this rural setting also achieved good mark academically, even though it was hampered by the pandemic. This study employed qualitative methods with a phenomenological approach, as the most relevant design for studying a life experience. Participants were four elementary school’s teachers in rural Tegal regency, Central Java. Data was gathered through an in-depth interview, and analyzed using the tradition of content analysis. Triangulation was conducted by interviewing significant others of each participant, to maintain the credibility of the data. The results of this study showed that all the subjects, reflecting that when facing obstacles during a pandemic, they were able to bring up a set of skills that a person uses when faced with challenging thoughts, feelings, emotions, and/or experiences. Themes emerged included struggle to adapt, such as “Create New Innovations to Address Solutions,